Sensory marketing for promoting more sustainable purchasing behaviour - Margarita Išoraitė; Daiva Aktas (Entrepreneurship and Sustainability Issues)
The article analyses sensory marketing to encourage more sustainable purchasing behaviour. The article uses the interview method to evaluate the use of sensory marketing elements to promote sustainability values. Sensory marketing affects sales and sustainability through enhanced consumer awareness of the importance of more socially responsible consumption. It is evident that the most influential of all the sensory marketing elements is sight (image), followed by hearing (sound), then smell (odour), touch (feel), and the least influential is taste (taste). According to respondents, it is acceptable that recycled materials are used to make reusable packaging, which ensures circular use of resources. Recycling gives waste a second life. Sustainable purchasing and consumption are reached by choosing products of higher quality and longer shelf life. Each person should decide whether they need a new product or service. Sensory marketing encourages a choice of higher quality, longer-lasting products. The findings show that socially responsible purchasing behaviour is still not a universal norm.